2017
DOI: 10.1016/j.ijheh.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient dichloromethane in pregnancy and infancy from industrial sources and childhood cancers in California

Abstract: Background The incidence of childhood cancers has been increasing, and environmental exposure to air toxics has been suggested as a possible risk factor. This study aims to explore ambient exposure to dichloromethane (methylene chloride). Methods We frequency matched by birth year approximately 20 cancer-free controls identified from birth records to all childhood cancers ages 0–5 in the California Cancer Registry diagnosed from 1988–2012; i.e. 13,636 cases and a total of 270,673 controls. Information on ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The CC cluster in this area can also be explained by multiple factors such as the proximity to high traffic roads with high flow of vehicles using diesel fuel; diesel is an agent defined as carcinogen by IARC, which has been found associated with CC 35 . Likewise, the high risk of CC in the industrial area might also be related with the occupational exposure of parents who live near the workplace; there are several authors who have found a relationship between CC and maternal or paternal occupation 36‐40 . In addition, other contaminants with other exposure routes could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The CC cluster in this area can also be explained by multiple factors such as the proximity to high traffic roads with high flow of vehicles using diesel fuel; diesel is an agent defined as carcinogen by IARC, which has been found associated with CC 35 . Likewise, the high risk of CC in the industrial area might also be related with the occupational exposure of parents who live near the workplace; there are several authors who have found a relationship between CC and maternal or paternal occupation 36‐40 . In addition, other contaminants with other exposure routes could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…As also for the permanent transit of this type of automotive in this area, due to the loading and unloading of merchandise in the industrial sources that are in this industrial agglomerate. Likewise, in this area of industrial agglomerate the exhibition may not be related to air emissions but to the occupational exposure of parents who live near the workplace; there are several authors who have found a relationship between childhood cancer and maternal or paternal occupation [40] [41] [42] [43] [44].…”
Section: Discussionmentioning
confidence: 99%
“…(5) Also, VOCs have been reported to cause health problems such as carcinogenesis after longterm exposure; thus, countermeasures are required. (6)(7)(8)(9)(10)(11)(12) If we can constantly monitor the types and concentrations of VOCs used in manufacturing processes and laboratories, we can maintain a safe work environment. In this study, polymer thin films that can detect VOCs were formed by plasma polymerization, and their gas adsorption characteristics and desorption were investigated using a quartz crystal microbalance (QCM).…”
Section: Introductionmentioning
confidence: 99%